Losing the News : the uncertain future of the news that feeds democracy - Jones, Alex S.; Annenberg Foundation Trust at Sunnylands; Annenberg Public Policy Center (New York : Oxford University Press, 2010)
The author, a Pulitzer Prize winning journalist explores how the epochal changes sweeping the media have eroded the core news that has been the essential food supply of our democracy. At a time of dazzling technological innovation, he says that what stands to be lost is the fact based reporting that serves as a watchdog over government, holds the powerful accountable, and gives citizens what they need. In a tumultuous new media era, with cutthroat competition and panic over profits, the commitment of the traditional news media to serious news is fading. Should we lose a critical mass of this news, our democracy will weaken and possibly even begin to fail. This book is also a call to arms. Despite the current crisis, there are many hopeful signs, and he closes by looking over the horizon and exploring ways the iron core can be preserved.--From publisher description
The iron core -- Media and democracy -- The fragile First Amendment -- Objectivity's last stand -- Media ethics: the painful balance -- The curious story of news -- Newspapers on the brink -- The new news media -- Saving the news
Subtitle on cover: The future of the news that feeds democracy
"The Annenberg Foundation Trust at Sunnylands, the Annenberg Public Policy Center of the University of Pennsylvania."
Includes index.
Keywords: Journalism -- Political aspects -- United States; Journalism -- Economic aspects -- United States; Journalism -- Objectivity -- United States; Journalistic ethics -- United States